Technological factors influencing e-invoice: Qualitative insights from Malaysia’s early implementation - Ilias, Azleen; Baidi, Nasrudin; Ghani, Erlane K.; Mohammad, Kamaruzzaman (Edelweiss Applied Science and Technology, 2025)
This paper applies the Technology-Organization-Environment (TOE) framework to examine e-invoicing adoption during Malaysia’s early implementation phase. Using a single case study involving large and small companies, along with accounting firms, tax freelancers, and consultants, the study identifies six key factors influencing adoption. It highlights three core technological drivers: system integration, middleware/Application Programming Interface (API) usage, and automation, aligning with TOE components and extending Rogers' Diffusion of Innovation (DOI) attributes. Challenges faced by adopters include system changes, validation delays, format incompatibility, and internet/server limitations. These issues particularly affect smaller enterprises with limited digital readiness. The findings underscore the need for targeted policy interventions and technical support to accommodate varying levels of digital maturity. Regulatory bodies and system providers are urged to simplify integration, offer affordable middleware solutions, and enhance user support. Addressing these technological hurdles is vital to improving compliance, inclusivity, and effectiveness within Malaysia’s digital tax infrastructure. This study contributes uniquely by identifying and analyzing the technological drivers and challenges to e-invoicing adoption, emphasizing practical implications for policymakers, developers, and organizations. By integrating insights from the TOE and DOI frameworks, it offers a comprehensive understanding of the technological landscape shaping Malaysia’s e-invoicing ecosystem.